2017
DOI: 10.1108/pr-04-2015-0085
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of perceived time pressure, satisfaction with work-family balance (SWFB), and leader-member exchange (LMX) on creativity

Abstract: Purpose Drawing on role theory, the purpose of this paper is to investigate a curvilinear relationship between employee’s perceived overall time pressure and creativity. Apart from this, it explores a three-way interaction of perceived time pressure, satisfaction with work-family balance (SWFB), and leader-member exchange (LMX) on creativity. Design/methodology/approach The paper reports a quantitative study of 251 employees from a European company. An online survey was used to collect data. The proposed hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 73 publications
(126 reference statements)
4
45
0
Order By: Relevance
“…The core contribution of this study lies in its elaboration of how three energy‐enhancing resources – passion for work, emotion sharing and organizational commitment – buffer the negative effect of employees' perceptions of work overload on their creative behaviours. The lack of previous attention to this influence is somewhat surprising, in light of the recognition that the energy‐depleting effects of demanding work conditions that make employees turn away from positive work behaviours can be countered by access to relevant resources (e.g., Bakker, Demerouti, & Euwema, ; Hakanen, Bakker, & Demerouti, ; Pooja et al, ), as well as calls for continued considerations of contingency factors that might influence the extent to which workload pressures inform creativity (e.g., Aleksić et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The core contribution of this study lies in its elaboration of how three energy‐enhancing resources – passion for work, emotion sharing and organizational commitment – buffer the negative effect of employees' perceptions of work overload on their creative behaviours. The lack of previous attention to this influence is somewhat surprising, in light of the recognition that the energy‐depleting effects of demanding work conditions that make employees turn away from positive work behaviours can be countered by access to relevant resources (e.g., Bakker, Demerouti, & Euwema, ; Hakanen, Bakker, & Demerouti, ; Pooja et al, ), as well as calls for continued considerations of contingency factors that might influence the extent to which workload pressures inform creativity (e.g., Aleksić et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of previous attention to this influence is somewhat surprising, in light of the recognition that the energy-depleting effects of demanding work conditions that make employees turn away from positive work behaviours can be countered by access to relevant resources (e.g., Bakker, Demerouti, & Euwema, 2005;Hakanen, Bakker, & Demerouti, 2005;Pooja et al, 2016), as well as calls for continued considerations of contingency factors that might influence the extent to which workload pressures inform creativity (e.g., Aleksić et al, 2017).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Servant leadership meta-analysis 41 Bambale, Shamsudin, and Subramaniam (2015) Jaramillo et al (2009) Siddiqi (2013) Bavik, Bavik, and Tang (2017) Johnson (2016) Trivers (2009) Bobbio, van Dierendonck, and Manganelli (2012) Liden et al (2015) Tuan (2017) Bouzari and Karatepe (2017) Liden et al (2008) van Dierendonck andNuijten (2011) Brubaker, Bocarnea, Patterson, and Malingumu, Stouten, Euwema, and Babyegeya (2016) Vondey (2010) Chen et al Gilmore, Hu, Wei, Tetrick, and Zaccaro (2013) Li, Yu, Yang, Qi, andFu (2014) Gong, Huang, andFarh (2009) LMX -Creativity Aleksi c, Miheli c, Cerne, and Skerlavaj (2017) Liao, Liu, and Loi (2010) Pan, Wu, Zhou, and Lou (2015) Chughtai (2016) Martinaityte and Sacramento (2013) Tierney, Farmer, and Graen (1999) Huang, Krasikova, and Liu (2016) Meng, Tan, and Li (2017) van Dyne, Jehn, and Cummings (2002) Jiang and Yang (2015) Muñoz-Doyague and Nieto (2012) Volmer, Spurk, and Niessen (2012) Joo ( …”
Section: Continuedmentioning
confidence: 99%
“…Thus, we expect that job characteristics can strengthen the likelihood that employees utilize their PsyCap to generate greater creativity. Finally, and importantly, although previous research has painted a comprehensive picture of employee (creative) performance, including all the characteristics of the workers, the working environment and the job (Steers & Porter, 1991), fewer empirical studies have simultaneously considered the various contextual factors (e.g., Aleksić, Mihelić, Ćerne, & Škerlavaj, 2017). Specifically, research based on leaders' situational influence (Kerr & Jermier, 1978) has shown that leader behaviours may influence subordinates' appraisal of their jobs (Smircich & Morgan, 1982).…”
Section: Introductionmentioning
confidence: 99%